Method of Strengthening Structure of Building - Nusa Setiani Triastuti (Applied Research on Civil Engineering and Environment (ARCEE), 2019)
The owner asks the author to see the condition of the commercial building. The author recognizes that Commercial Buildings do not meet the requirements of the structure of strength, stability, and stiffness. Of the substructure and upper structure of commercial buildings in the business center in Riau Province. Even though they have been built, they do not meet the structural requirements. A thorough analysis is needed from the bottom structure to the top structure. This research aim is strengthening under and upper structure, nothing moving the user and operational — survey methodology with collecting primary and secondary data. Substructure and upper structure data are analyzed for the cause of the damage. The solution is the design and construction stages — design of substructure and upper structure strengthening. The right construction stage applies for an essential role in the success of the construction because the condition of the existing structure from the bottom up is weak. The structural improvement achieved successful results.